Practices of responsability and aesthetics of decontamination in the work of “Reflektor Teatar” (Itinera, 2019)
The article focuses on the work of the Serbian theatrical company Reflektor Teatar. Through the analysis of Macho Men, a documentary play about the manhood in contemporary Serbia, the author highlights and explains the role of responsibility of both, the sender and the receiver of the artistic message in the process of cultural decontamination. The key concept is the idea of catharsis and education through theatre used as instruments for fostering changes and bettering the social context considered.